Μ‐Chlorido‐Bridged Dimanganese(II) Complexes of the Schiff Base Derived from [2+2] Condensation of 2, 6‐Diformyl‐4‐methylphenol and 1, 3‐Bis(3‐aminopropyl)tetramethyldisiloxane: Structure, Magnetism, Electrochemical Behaviour, and Catalytic Oxidation of Secondary Alcohols. Issue 1 (22nd November 2013) - Alexandru, Mihaela; Cazacu, Maria; Arvinte, Adina; Shova, Sergiu; Turta, Constantin; Simionescu, Bogdan C.; Dobrov, Anatolie; Alegria, Elisabete C. B. A.; Martins, Luísa M. D. R. S.; Pombeiro, Armando J. L.; Arion, Vladimir B.
Abstract: The reaction of 2, 6‐diformyl‐4‐methylphenol with 1, 3‐bis(3‐aminopropyl)tetramethyldisiloxane in the presence of MnCl2 in a 1:1:2 molar ratio in methanol afforded a dinuclear μ‐chlorido‐bridged manganese(II) complex of the macrocyclic [2+2] condensation product (H2 L), namely, [Mn2 Cl2 (H2 L)(HL)]Cl· 3H2 O (1 ). The latter afforded a new compound, namely, [Mn2 Cl2 (H2 L)2 ][MnCl4 ]· 4CH3 CN· 0.5CHCl3 · 0.4H2 O (2 ), after recrystallisation from 1:1 CHCl3 /CH3 CN. The co‐existence of the free and complexed azomethine groups, phenolato donors, μ‐chlorido bridges, and the disiloxane unit were well evidenced by ESI mass spectrometry and FTIR spectroscopy and confirmed by X‐ray crystallography. The magnetic measurements revealed an antiferromagnetic interaction between the two high‐spin ( S = 5/2, g = 2) manganese(II) ions through the μ‐chlorido bridging ligands. The electrochemical behaviour of1 and2 has been studied, and details of their redox properties are reported. Both compounds act as catalysts or catalyst precursors in the solvent‐free low‐power microwave‐assisted oxidation of selected secondary alcohols, for example, 1‐phenylethanol, cyclohexanol, 2‐ and 3‐octanol, to the corresponding ketones in the absence of solvent. The highest yield of 72 % was achieved for 1‐phenylethanol by using a maximum of 1 % molar ratio of catalyst relative to substrate. Abstract : Two μ‐chlorido‐bridged dimanganese(II) complexes with disiloxane‐containing macrocyclic ligands act as catalyst precursors in the solvent‐free low‐power microwave‐assisted oxidation of selected secondary alcohols.